STUDENT MOBILITY: FACTORS FOR CHOOSING INDONESIA AS A STUDY ABROAD DESTINATION - Fajarwati, Indah; Suyanto, A (PEOPLE: International Journal of Social Sciences, 2019)
The Indonesian government encourages the process of internationalization of higher education by increaseing the number of foreign students studying in Indonesia. However, based on UNESCO student flow data in 2018, it can be concluded that Indonesia is not yet a popular study destination for students even in the ASEAN. Therefore it is necessary to investigate the factors that drive foreign students to choose Indonesia as their education location. The factors examined are: Country Environment with sub variables perception about Indonesia, academic quality, environment (climate and weather), marketing programs, immigration process, opportunities to learn language and culture, Institutional characteristics with sub variable programs offered, significant others who influence country choice, creative capital, significant others who influence university selection, university academic quality, financial assistance/scholarships, interaction with lecturers and research topics, university location, City Location with sub variable diversity, level of tolerance and nondiscrimination factors. Data were collected through questionnaires to 106 foreign students studying in Indonesia. The data analysis technique used Principal Component Analysis (CPA). The results show that there are 2 new factors namely academic and scholarship factor and geographic and bilateral relationships factor that are considered by foreign students to choose Indonesia as their study destination.